Evaluation of cocoa plus trees (Theobroma cacao L.) for high yield in Coimbatore plantations - Boomiga, M; Jegadeeswari, V; Balakrishnan, S; Jeyakumar, P (Journal of Plantation Crops, 2018)
A survey was conducted in cocoa growing areas of Coimbatore district of Tamil Nadu for identifying the high yielding plus trees to increase the production and productivity of cocoa in Tamil Nadu. Thirty five high yielding plus trees were screened from farmer’s field and yield characters were recorded. Maximum flowering was observed in Tc (Vedapatti) 62 while the pod set percentage was high in Tc (Vedapatti) 2. Pod weight, single dry bean weight and dry bean weight per pod was maximum in Tc (Vedapatti) 99 while Tc (Vedapatti) 72 recorded higher number of beans pod–1 and dry bean yield tree–1. This study shows the variability among the plus trees and the identified well performing plus trees can be used in breeding programs to get sustainable yield in cocoa.